Case Report: An exceptional response to neoadjuvant radiotherapy and chemotherapy in undifferentiated pleomorphic sarcoma following checkpoint inhibitor use - Jeon, Won Jin; Moon, Jin Hyun; Pham, Bryan; Joung, Bowon; Denham, Laura; Brothers, Joel (Frontiers in Oncology, 2023)
Undifferentiated pleomorphic sarcoma (UPS), a subtype of soft tissue sarcoma (STS), is an uncommon malignancy associated with poor prognosis. As with other forms of sarcomas, surgical resection remains the only form of treatment with curative potential. The role of perioperative systemic therapy has not been definitively elucidated. Due to high recurrence rates and metastatic potential, the management of UPS can pose a difficult task for clinicians. In cases of unresectable UPS due to anatomic limitations and in patients with comorbidities and poor performance status (PS), management options are limited. We describe a patient with UPS involving the chest wall with poor PS who achieved complete response (CR) following neoadjuvant chemotherapy and radiation in the setting of prior immune-checkpoint inhibitor (ICI) therapy.